Mobile Devices Applied in Self-Studying English as a Foreign Language Among Non-Native Students in Vietnam and Japan - Nguyen, Thuy Thi Thanh; Takashi, Yukawa (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Abstract – In the era of technology, learning can be supported with mobile devices inside and outside of the classroom. In the hope of taking advantage of technology advances, teachers worldwide have integrated technologies into teaching to effectively deliver lesson content and address students’ needs. However, few non-native learners are exposed to mobile devices to optimize self-studying English outside the classroom. Thus, the present paper conducts a case study to look into mobile devices’ applications to enhance self-studying English as a foreign language. The study participants included 26 Japanese and Vietnamese learners divided into two groups over 15 weeks. Quantitative and qualitative methods were used to analyze and compare the results with R-Studio statistics software. The present study sought to encourage collaboration and foster the autonomy of learners with mobile devices’ assistance as supporting language self-learning tools. The findings of the present research will be discussed in terms of the efficiency and potentials of mobile devices as supportive tools outside of classroom activities among Vietnamese and Japanese students as non-native learners of English.